Uso de Nematodos entomopatógenos para el control de insectos en cultivos de Hortalizas - Zambrano Zambrano, David Alexander (2024)
This research focused on the use of entomopathogenic nematodes for pest control in vegetable crops, addressing their identification, mechanisms of action, efficiency, and environmental impact. The general objective was to describe their use, while the specific objectives included identifying the main entomopathogenic nematodes, detailing their control mechanisms, and analyzing their efficiency under different conditions and crops. The methodology used consisted of an exhaustive review of scientific literature. The results revealed that the genera Steinernema and Heterorhabditis are the main entomopathogenic nematodes used, due to their high effectiveness against a variety of pest insects. The control mechanisms include infecting the host by releasing symbiotic bacteria, causing the insect's death within a few days. The efficiency of these nematodes can reach up to 50% pest reduction under optimal conditions, although factors such as soil temperature and humidity can significantly influence their performance. Regarding environmental impact, the use of entomopathogenic nematodes presents a lower risk compared to chemical pesticides, as they do not leave toxic residues and are safe for non-target organisms. The main conclusions of the research underscore the effectiveness and sustainability of entomopathogenic nematodes as a viable alternative for pest management in vegetable crops. Additionally, the need for further research to optimize application conditions and maximize efficiency in various agricultural contexts is highlighted